Diatom frustules protect DNA from ultraviolet light - Aguirre, Luis Ever (Sci Rep, 2018)
The evolutionary causes for generation of nano and microstructured silica by photosynthetic algae are not yet deciphered. Diatoms are single photosynthetic algal cells populating the oceans and waters around the globe. They generate a considerable fraction (20–30%) of all oxygen from photosynthesis, and 45% of total primary production of organic material in the sea. There are more than 100,000 species of diatoms, classified by the shape of the glass cage in which they live, and which they build during algal growth. These glass structures have accumulated for the last 100 million of years, and left rich deposits of nano/microstructured silicon oxide in the form of diatomaceous earth around the globe. Here we show that reflection of ultraviolet light by nanostructured silica can protect the deoxyribonucleic acid (DNA) in the algal cells, and that this may be an evolutionary cause for the formation of glass cages.